1981
DOI: 10.1007/bf00236258
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical localization of gonadotropin-releasing hormone (GnRH) in the brain and infundibulum of the sheep

Abstract: The distribution of gonadotropin-releasing hormone (GnRH) was studied in the brain and infundibulum (INF) or median eminence of sheep utilizing a peroxidase-antiperoxidase immunohistochemical method. This procedure utilized a specific antiserum generated against GnRH conjugated to bovine serum albumin. In the rostral INF, the greatest concentration of GnRH positive axons was found in the medial region, mostly in the external layer dorsal to the hypophysial portal plexus. In the intermediate portion of the INF,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
10
0
13

Year Published

1981
1981
2007
2007

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 21 publications
3
10
0
13
Order By: Relevance
“…However, in addition to populations of singlelabeled OFQ cells in these areas, we found an exceptionally high percentage of GnRH-ir cells that colocalized OFQ. Double-labeled OFQ/GnRH cells were not regionally restricted, and a similar high percentage of colocalization (Ͼ90%) was seen in each brain region in which GnRH cells are found (Table 1), even though the total number of GnRH neurons in each region varied as expected (22,31,32). The high percentage of colocalization suggests that OFQ is functionally important in the control of GnRH secretion.…”
Section: Discussionmentioning
confidence: 65%
“…However, in addition to populations of singlelabeled OFQ cells in these areas, we found an exceptionally high percentage of GnRH-ir cells that colocalized OFQ. Double-labeled OFQ/GnRH cells were not regionally restricted, and a similar high percentage of colocalization (Ͼ90%) was seen in each brain region in which GnRH cells are found (Table 1), even though the total number of GnRH neurons in each region varied as expected (22,31,32). The high percentage of colocalization suggests that OFQ is functionally important in the control of GnRH secretion.…”
Section: Discussionmentioning
confidence: 65%
“…Immunocytochemical analysis has revealed that the distribution of LHRH neurons forms a loosely arranged continuum in the diagonal band of Broca, organum vasculosum of the lamina terminalis (OVLT), medial preoptic area (POA), and the rostral-most anterior hypothalamus in the bovine brain [6,7]. A similar distribution of LHRH neurons was reported in the sheep [8,9].…”
Section: Introductionmentioning
confidence: 59%
“…A recent study which utilized the same antiserum for immunocytochemical procedures in the rat also failed to visualize reactive perikarya [17]. However, immunoreactive LHRH containing perikarya have been localized with this antiserum in the horse [11], sheep [12], and cow [10].…”
Section: Discussionmentioning
confidence: 99%
“…Prior to its use in each as say, the antiserum was preabsorbed with I mg BSA/0.1 ml BSA/0.1 ml 1:100 antiserum (12 h, 4°C) in order to remove any anti-BSA activity. Control procedures to verify the LHRH localiz ing reaction were as described previously by Dees et al [ 12].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation